Buyer Uncertainty About Seller Capacity: Causes, Consequences, and a Partial Solution - Horton, John J. (Management Science, 2019)
Employers in an online labor market often pursue workers with little capacity to take on more work. The pursuit of low-capacity workers is consequential, as these workers are more likely to reject employer inquires, causing a reduction in the probability that a job opening is ultimately filled. In an attempt to shift more employer attention to workers with greater capacity, the market-designing platform examined in this paper introduced a new signaling feature into the market. It was effective, in that when a worker signaled having high capacity, he or she received more invitations from employers, rejected a smaller fraction of those invitations, quoted lower prices to do the work, and was more likely to be hired. A back-of-the-envelope calculation suggests the signaling feature alone could increase market surplus by as much as 6%, both by increasing the number of matches formed and by helping to allocate projects to workers with lower costs. This paper was accepted by Lorin Hitt, information systems.